Hepatocyte growth factor/scatter factor induces VEGF in human external auditory canal cholesteatoma cell culture - Naim, Ramin; Sadick, Haneen; Bayerl, Christiane; Riedel, Frank; Schäfer, Carsten; Bran, Gregor M.; Hörmann, Karl (International journal of molecular medicine, 2005)
Human external auditory canal cholesteatoma (EACC) is not often seen in otolaryngology. Some authors have noted circulatory disorders of the local blood vessels as the etiologic factor for establishing EACC. Diminished oxygen supply results in the attempt to establish angiogenesis. Hepatocyte growth factor/scatter factor (HGF/SF) and vascular endothelial growth factor (VEGF) are the most important angiogenic factors in this process. In a recent study we described strong expression of VEGF and HGF in EACC. All EACC and normal AMS cell cultures were obtained from 5 patients undergoing surgery and used at passage 3. After 16 to 72 h of incubation with 20 ng/ml HGF/SF, the expression of the VEGF protein in the supernants of the HGF/SF-treated and untreated culture was analyzed. EACC-culture cells showed a stronger baseline expression of VEGF. After 72 h of incubation with 20 ng/ml HGF/SF of HGF/SF, the expression of VEGF in normal keratinocytes was 173.4 pg/ml. The expression level of VEGF in the EACC culture was 275.73 pg/ml. We observed a 2.5-fold induction of VEGF in EACC after 72 h, which started with 1.5-fold baseline VEGF concentrations of normal keratinocytes. Our analysis showed that, in the EACC culture, VEGF was elevated after treatment with HGF/SF. HGF/SF appears to activate cellular pathways inducing release of VEGF. After purification, no fibroblasts were present in our EACC culture so as to exclude possible paracrine effects by fibroblasts.
Gesehen am 25.03.2022